Framing Election Fraud in Indonesia's 2024 Elections: A Comparative Analysis of Tempo.co and Republika.com - Subagyo, Hafshah Nurqaidah; Alwaton, Yogie (Universitas Ahmad Dahlan, 2024)
Election fraud is a topic that has become an interesting discussion in the 2024 elections. The mass media will certainly not miss the discussion on the topic of election fraud. Two major mass media in Indonesia, Tempo.co and Republika.com also reported news about election fraud. This study aimed to narrate the topic of election fraud in the two media. This research was analyzed using Robert N. Entman's framing analysis method. Primary data was collected from news in Tempo.co and Republika.com regarding alleged election fraud in the March 2024 period. The results of this study show that Tempo.co framed by indicating the existence of election fraud and was caused by various things such as money politics, ethical violations, and the loss of neutrality of election organizers. Meanwhile, Republika.com considers that the alleged election fraud causes doubts about the election results so the right of inquiry and a lawsuit to the Constitutional Court can be a solution to resolve the General Election Results Dispute (PHPU).